Effects of exercise/physical activity on fear of movement in people with spine-related pain: a systematic review - Jadhakhan, Ferozkhan; Sobeih, Raghip; Falla, Deborah (Frontiers in Psychology, 2023)
Background: Kinesiophobia (i.e., fear of movement) can be an important contributor for ongoing pain and disability in people with spine-related pain. It remains unclear whether physical activity interventions/exercise influence kinesiophobia in this population. A systematic review was therefore conducted to synthesise the available evidence on whether physical activity interventions/exercise influence kinesiophobia in people with chronic nonspecific spine-related pain.: The study protocol was registered prospectively with PROSPERO (CRD42021295755). The following databases were systematically searched from inception to 31 st January 2022 and updated on 22 nd June 2023: PubMed, MEDLINE, Embase, CINAHL, Web of Science, PsycINFO, ZETOC, PROSPERO and Google Scholar. Inclusion criteria were randomised or non-randomised controlled studies investigating adults aged ≥18 years, reporting the effect of exercise or physical activity on kinesiophobia in individuals with chronic non-specific spine-related pain. Two reviewers independently extracted data and assessed the quality of the included studies. Bias was assessed using the Cochrane ROB2 tool and evidence certainty via Grading of Recommendations Assessment, Development and Evaluation (GRADE).Results: Seventeen studies from seven countries involving a total of 1,354 individuals were selected for inclusion. The majority of studies (n=13) involved participants with chronic low back pain (LBP), and Pilates was the most common form of exercise evaluated. Most of the studies reported a positive direction of effect in favour of exercise reducing kinesiophobia when compared to a control group. There was moderate to high risk of bias among the studies and the overall certainty of the evidence was very low.3 Conclusion: This review supports the use of exercise for reducing kinesiophobia in people with chronic LBP albeit with very low certainty of evidence; Pilates (especially equipmentbased) was shown to be effective as were strengthening training programmes. There was limited evidence available on the effects of exercise on kinesiophobia for people with chronic neck or thoracic pain and further research is required.